Drone technology in agriculture - Dhulipala, Ram (International Livestock Research Institute, 2022)
CGIAR Research Initiative on Digital Innovation collaborated with Clearskies Learning & Research Pvt. Ltd to organize a three-day “Awareness Webinar on Drone Technology in Agriculture” for the Initiative's stakeholders in South Africa between November 28-30, 2022. The South-South training program was moderated by Capt. Gaurav Nath (Founder & CEO, Clearskies) and Mrs. Akshatha Annaiah (Consultant, ILRI). The webinar had in-house experts from Clearskies located in Bengaluru, India, and experienced drone professionals from the Indian drone industry. This video recording was made from the webinar.